Punir e remir: as dinâmicas que permeiam o direito à remição da pena através da leitura no sistema prisional brasileiro - Macacari, Otávio (Universidade Federal de São Carlos, 2023)
The present work seeks to understand the dynamics surrounding the right to sentence remission through reading in the Brazilian prison system. Through this process, Brazilian inmates can reduce their days of sentence by writing reviews of literary works read during their period of incarceration. In dialogue with international literature on punishment and also with authors addressing the Latin American context, the objective was to map the processes that surround the right to sentence remission through reading. To achieve this, in addition to discussing the literature on the subject, a survey of the history of the right in question was conducted up to the present day, along with interviews with individuals who, in some way, have a connection to it. Through bibliographic data, quantitative analysis, and interviews with individuals involved in remission practices, it was possible to observe that the right in question has shown good theoretical development, especially in recent decades, but limited practical development. Furthermore, it was noted that the practice of reading primarily reaches individuals with advanced educational levels, restricting itself to a small portion of the prison population.
Remission and punition: the dynamics surrounding the right to sentence remission through reading in the Brazilian prison system
Keywords: Remição; Leitura; Punição; Sistema prisional; Remission; Reading; Punishment; Prison system; CIENCIAS HUMANAS::SOCIOLOGIA